Lasers in Dermatology: Parameters and Choice With Special Reference to the Asian Population - Lee, Jae Dong.; Oh, Min Jin Maya.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
In the book of 'Lasers in Dermatology: Parameters and Choice,' specific laser parameters are described around each laser instrument for these novices. However, since it is impossible to treat effective and safe laser simply by memorizing parameters, it is described based on the important principles that is essential for parameter control. This book describes a total of 13 lasers and energy-based devices : Q-switched ruby laser, Q-switched Nd:YAG laser, picosecond alexandrite laser, long-pulsed Nd:YAG laser, pulsed-dye laser, intense pulsed light (IPL), long-pulsed alexandrite laser, Er:YAG laser, CO2 fractional laser, fractional microneedle radiofrequency (RF), light-emitting diode (LED), skin equipment, and 1,450nm diode laser. And for novices, it explains the simple principles of lasers and the concepts you need to know when you start skin care and laser. It also explains the treatment of scars and melasma, which are the diseases that novices are most interested in. Finally, it describes post-inflammatory (PIH) and side effects and complications that novices are embarrassed about in diagnosis and treatment.
I. Principles of Laser -- 1. Six parameters of lasers in dermatology -- II. Choice of laser and medical skin care -- 2. Choice of laser -- 3. Medical skin care -- III. Lasers and parameters -- 4. Q-switched Ruby laser and absorption coefficient -- 5. Q-switched Nd:YAG laser and subcellular selective photothermolysis -- 6. Alexandrite picosecond laser and stress confinement time -- 7. Long-pulsed Nd:YAG laser and Arrhenius equation -- 8. Pulsed-dye laser and macropulse -- 9. Intense pulsed light and extended theory of selective photothermolysis -- 10. Long-pulsed alexandrite laser and thermal kinetic selectivity -- 11. CO2, Er:YAG laser and residual thermal damage -- 12. CO2 fractional laser and fractional photothermolysis -- IV. Energy-based devices and parameters -- 13. Fractional microneedle radiofrequency and conductivity -- 14. Light emitting diode and Arndt-Schultz curve -- 15. Skin care equipment and calcium gradient -- V. Treatment of acne, scar and melasma -- 16. Photodynamic therapy and consensus of acne treatment -- 17. Acne atrophic scar and hisology -- 18. Melasma and melanogenesis -- VI. Complications of laser treatment -- 19. Pathogenesis and treatment of post-inflammatory hyperpigmentation -- 20. Complications and its treatment in laser treatment.
Keywords: Dermatology; Dermatology; Skin Diseases -- surgery; Laser Therapy -- methods; Cosmetic Techniques; Asian People